2019
DOI: 10.1007/s13224-019-01272-w
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone Values in Pregnancy: Cutoff Controversy Continues?

Abstract: Thyroid disorders in pregnancy are important causes of adverse pregnancy outcome. So it is very pertinent that thyroid function is maintained in normal range during pregnancy. Serum thyroid-stimulating hormone (TSH) value is the best indicator for assessing and monitoring thyroid function. The increasing metabolic demands of pregnancy alter the thyroid physiology in early pregnancy; hence, it becomes necessary to define trimester-specific reference range. Several reports and guidelines have been published reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
0
20
1
1
Order By: Relevance
“…1 The cut-off of 2.5 mIU/L in first trimester as recommended by ATA in 2011 was not accepted in many studies. 3,6,8,10,12,13 Looking at the Indian scenario, the current evidence is conflicting. Indian reports analysed by Kalra et al, stated that cut off of 4.0 mIU/L may be too high for Indian women and they suggested an intermediate cut off of 3.0 mIU/L for first trimester and 3.5 mIU/L for second and third trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The cut-off of 2.5 mIU/L in first trimester as recommended by ATA in 2011 was not accepted in many studies. 3,6,8,10,12,13 Looking at the Indian scenario, the current evidence is conflicting. Indian reports analysed by Kalra et al, stated that cut off of 4.0 mIU/L may be too high for Indian women and they suggested an intermediate cut off of 3.0 mIU/L for first trimester and 3.5 mIU/L for second and third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…The major obstetric complications are miscarriage, pre-eclampsia and its associated complications, preterm labour and the fetal complications are prematurity, low birth weight, still birth and perinatal death. [3][4][5] Severe maternal hypothyroidism can result in irreversible neurological deficit in the offspring. One in ten women develop TPO antibodies and hypothyroidism develops in 16% of these women.…”
Section: Introductionmentioning
confidence: 99%
“…I am extremely happy to share with you all that the accesses of my articles have crossed unprecedented "40,000" mark as of November 2020. In my first year, I wrote my editorial series on medical writing and ethical aspects of medical writing [2][3][4][5][6][7], second year, I chose the editorial series on gyn-endocrinology [8][9][10][11][12][13], a topic close to my heart, and third year, I had a few guest editorials and some miscellaneous topics of common interest [14][15][16][17][18].…”
Section: Editorialsmentioning
confidence: 99%
“…Musculoskeletal Disorders and Menopause [9] became the most popular article with the top most full text requests, whereas Thyroid-Stimulating Hormone Values in Pregnancy: Cutoff Controversy Continues? [12] became the most popular article with 13,000 + accesses, highest ever in the history of JOGI.…”
Section: Popularity Of the Articlesmentioning
confidence: 99%
“…Hernandez and coworkers [ 33 ] found an increased risk of perinatal loss, miscarriage and premature birth for patients between 2.5 mIU/L and 4.0 mIU/L. In some countries, the authors concluded that 2.5 mIU/L is a low upper limit for first trimester pregnancy, with suggestions of an increase in the Indian population [ 34 ], the Chinese population [ 35 ], the Brazilian population (2.7 mIU/L) [ 36 ] and the Spanish population (4.72 mIU/L) [ 37 ]. Given the lack of information about the first trimester of pregnancy, this study addresses the creation of groups considering thyroid risk factors through clustering.…”
Section: Introductionmentioning
confidence: 99%